Evaluation of the Precision of Ancestry Inferences in South American Admixed Populations - Pereira, Vania; Santangelo, Roberta; Børsting, Claus; Tvedebrink, Torben; Almeida, Ana Paula F.; Carvalho, Elizeu F.; Morling, Niels; Gusmão, Leonor (Frontiers in Genetics, 2020)
Ancestry informative markers (AIMs) are used in forensic genetics to infer biogeographical ancestry of individuals and may also have a prominent role in future police and identification investigations. In the last few years, many studies have been published reporting new AIM sets. These sets include markers (usually around 100 or less) selected with different purposes and different population resolutions. Regardless of the ability of these sets to separate populations from different continents or regions, the uncertainty associated with the estimates provided by these panels and their capacity to accurately report the different ancestral contributions in individuals of admixed populations has rarely been investigated. This issue is addressed in this study by evaluating different AIM sets. Ancestry inference was carried out in admixed South American populations, both at population and individual levels. The results of ancestry inferences using AIM sets with different numbers of markers among admixed reference populations were compared. To evaluate the performance of the different ancestry panels at the individual level, expected and observed estimates among families and their offspring were compared, considering that 1) the apportionment of ancestry in the offspring should be closer to the average ancestry of the parents, and 2) full siblings should present similar ancestry values. The results obtained illustrate the importance of having a good balance/compromise between not only the number of markers and their ability to differentiate ancestral populations, but also a balanced differentiation among reference groups, to obtain more precise values of genetic ancestry. This work also highlights the importance of estimating errors associated with the use of a limited number of markers. We demonstrate that although these errors have a moderate effect at the population level, they may have an important impact at the individual level. Considering that many AIM-sets are being described for inferences at the individual level and not at the population level, e.g. in association studies or the determination of a suspect's biogeographical ancestry, the results of this work point to the need of a more careful evaluation of the uncertainty associated with the ancestry estimates in admixed populations.